2024
DOI: 10.1161/circulationaha.123.065657
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcification: Current Concepts and Clinical Implications

Carlotta Onnis,
Renu Virmani,
Kenji Kawai
et al.

Abstract: Coronary artery calcification (CAC) accompanies the development of advanced atherosclerosis. Its role in atherosclerosis holds great interest because the presence and burden of coronary calcification provide direct evidence of the presence and extent of coronary artery disease; furthermore, CAC predicts future events independently of concomitant conventional cardiovascular risk factors and to a greater extent than any other noninvasive biomarker of this disease. Nevertheless, the relationship between CAC and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Atherosclerosis forms the pathogenetic basis of CHD, characterized by endothelial injury, inflammation, and endothelial cell apoptosis ( 104 ). Coronary artery calcification (CAC) typically accompanies advanced atherosclerosis development and serves as a predictor of future cardiovascular events ( 105 ). Uromodulin has been shown to be an inhibitor of calcification in blood and urine, reducing the risk of calcification ( 25 , 106 ).…”
Section: Relationship Between Uromodulin and Various Cardiovascular D...mentioning
confidence: 99%
“…Atherosclerosis forms the pathogenetic basis of CHD, characterized by endothelial injury, inflammation, and endothelial cell apoptosis ( 104 ). Coronary artery calcification (CAC) typically accompanies advanced atherosclerosis development and serves as a predictor of future cardiovascular events ( 105 ). Uromodulin has been shown to be an inhibitor of calcification in blood and urine, reducing the risk of calcification ( 25 , 106 ).…”
Section: Relationship Between Uromodulin and Various Cardiovascular D...mentioning
confidence: 99%
“…Vascular diseases, particularly cardiovascular and brain diseases, are the leading causes of human disease mortality. Vascular calcification (VC) is considered a common pathological process in various vascular diseases, such as diabetes ( 1 ), atherosclerosis ( 2 , 3 ), vascular injury ( 4 , 5 ), chronic kidney disease (CKD) ( 6 ), liver fibrosis ( 7 ), and aging ( 8 ), and is closely associated with chronic calcium-phosphate deposition in blood vessels ( 9 , 10 ). Intimal calcification and medial calcification are two types of VC; the former is closely related to the infiltration of inflammatory cells, vascular inflammation, lipid deposits, hyperlipidemia, and hypertension, and the latter is associated with aging, diabetes, CKD, and arterial stiffness ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although epidemiological studies have revealed potential associations between these calcifications and metabolic disorders such as DM and altered glycemic traits, the underlying mechanisms driving this association remain complex, multifaceted, and inadequately understood [ 9 , 10 ]. Additionally, retrospective and prospective analyses have revealed that obesity, smoking, and hypertension are also associated with an increased risk of vascular and valvular calcifications [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%